Protective effects of the biofloc system in Pacific white shrimp (Penaeus vannamei) culture against pathogenic Vibrio parahaemolyticus infection. Issue 124 (May 2022) - Gustilatov, Muhamad; Widanarni,; Ekasari, Julie; Pande, Gde Sasmita Julyantoro
Abstract: The mitigation of vibriosis in shrimp culture could be accomplished by reducing the virulence of the pathogen or by increasing the immune response of the shrimp. This study aims to evaluate the application of a biofloc system in protecting Pacific white shrimp ( Penaeus vannamei ) from pathogenic Vibrio parahaemolyticus infection. Shrimp post-larvae (PL 20) with an average body weight of 0.041 ± 0.019 g were reared in an aquarium with a working volume of 33 L at a density of 3 L −1 for 21 days using two rearing systems, i.e., the biofloc system and the regular clear water system as control. In each system, the shrimp post-larvae were challenged by adding V. parahaemolyticus at different densities, 10 3, 10 5, and 10 7 CFU mL −1, while the negative control was performed by maintaining shrimp post-larvae in the clear water system without the addition of V. parahaemolyticus . The results of the in vitro experiment showed that the density and biofilm activity of V. parahaemolyticus reared in biofloc suspension was lower than that of the positive control (p < 0.05). The density of V. parahaemolyticus in shrimp rearing water was lower than that in the control at 10 5 CFU mL −1, especially on the 3rd day post-challenge, but there was no significant difference in the total presumptive Vibrio count between the biofloc treatment and the control. The survival, growth, and immune response parameters, such as total hemocyte count, phagocytic activity, respiratory burst, and phenoloxidase activity, of the shrimp, reared in the biofloc system were also higher than those of the positive control (p < 0.05), regardless of the density of V. parahaemolyticus . The present study demonstrated that the application of biofloc could significantly protect and increase the resistance of Pacific white shrimp against pathogenic V. parahaemolyticus infection. Highlights: Biofloc reduces the biofilm activity and density of Vibrio parahaemolyticus . Biofloc can act as a bacterial antivirulence, and protect shrimp from pathogenic Vibrio parahaemolyticus up to 10 7 CFU mL −1 Shrimp reared in biofloc systems have higher immune response, growth, and survival.